Autologous engineering of cartilage - Emans, Pieter J. (National Academy of Sciences, 2010)
Treatment of full-thickness damage to hyaline cartilage is hampered by the limited availability of autologous healthy cartilage and the lengthy, cost-prohibitive cell isolation and expansion steps associated with autologous cartilage implantation (ACI). Here we report a strategy for de novo engineering of ectopic autologous cartilage (EAC) within the subperiosteal space (in vivo bioreactor), through the mere introduction of a biocompatible gel that might promote hypoxia-mediated chondrogenesis, thereby effectively overcoming the aforementioned limitations. The EAC is obtained within 3 wk post injection of the gel, and can be press-fit into an osteochondral defect where it undergoes remodeling with good lateral and subchondral integration. The implanted EAC showed no calcification even after 9 mo and attained an average O’Driscoll score of 11 (versus 4 for controls). An “on demand” autologous source of autologous cartilage with remodeling capacity is expected to significantly impact the clinical options in repair of trauma to articular cartilage.